Histología y morfometría del ojo del pez dulceacuícola Paracheirodon axelrodi (Characiformes: Characidae) - Mario O Tovar; Martha J Obando; Edwin Gómez; María L Caldas; Hernán Hurtado (Revista de Biología Tropical, 2009)
El pez dulceacuícola P. axelrodi es de gran importancia comercial en la Orinoquía Colombiana y a nivel mundial, pero carece de estudios acerca de su visión. Se utilizaron diez individuos, con longitud total promedio de 2.7 cm (SD= 0.2, n= 20). Se realizaron cortes a 8 μm y se tiρeron con H-E. El tamaρo relativo del ojo es 9.8% (SD= 1.1, n= 20); el cristalino tiene un tamaρo relativo de 64.3% (SD= 4.9, n=20). Una esclerótica con tejido cartilaginoso. La retina está constituida por ocho capas y dos membranas, hay areae centrales en la zona posterior, por lo tanto tiene mayor espesor que la zona lateral. El espesor promedio de las estructuras es: retina lateral: 144.5 μm (SD= 5.4, n= 20), retina temporal: 210.4 μm (SD= 14.8, n= 20); cristalino (esfιrico): dorso-ventral 759.6 μm (SD= 31.7, n= 20) y antero- posterior 763.4 μm (SD= 30.7, n= 20) y cσrnea: 27.6 μm (SD= 4.3, n= 20). El tamaρo relativo del ojo, relacionado con la presencia de areae centrales y una córnea delgada, muestra las necesidades visuales del neón cardenal (cazador) para adaptarse al hábitat, lo que hace necesario tener un sistema visual desarrollado que le permita tener mejor sensibilidad y resolución visual. Histology and morphometry of the eye in the freshwater Paracheirodon axelrodi (Characiformes: Characidae). The visual system of Teleost fishes has a wide range of adaptations. The eye has suffered modifications, mainly towards better sensitivity and visual resolution according to specific environmental conditions. In that way, this organ is so important for survival. In spite of being the most commercialized Orinoquía species, and one of the most important ornamental fish worldwide, there are almost no studies on the communication systems of P. axelrodi (including vision). We studied the eye in ten individuals of P. axelrodi, with a mean total length of 2.7 cm (SD= 0.2, n= 20). We measured eye relative size (TRO) after sacrifice. Heads were processed for hematoxylin-eosin, and 8 μm thick sections were obtained. Images were digitalized for histological identification and morphometrics. The relation between TRO and body length was 9.8% (SD= 1.1, n= 20); lens was spherical with a relative size of 64.3% (SD= 4.9, n= 20). Rete mirabilis choroid was composed mainly by capillaries, while sclera was composed of cartilaginous tissue. Retina with eight layers and two membranes. An areae centrales was observed in the posterior retina. Iris covered by a simple cubic epithelium. Cornea of endothelial tissue with two membranes. Pupil almost circular, with a naso-caudal elongation. Measures of retina thickness were as follows: lateral retina 144.5 μm (SD= 5.4, n= 20), temporal retina 210.4 μm (SD= 14.8, n= 20). Lens measurements were: dorso- ventral 759.6 μm (SD= 31.7, n= 20), antero-posterior 763.4 μm (SD= 30.7, n= 20). Cornea thickness was 27.6 μm (SD= 4.3, n= 20); iris thickness was 18.9 μm (SD= 1.9, n= 20); rete mirabilis choroid 22.2 μm (SD= 3.2, n= 20) and sclera: 15.9 μm (SD= 1.2, n= 20). This species has a typical Teleost eye conformation. The retina was thicker in the posterior area, probably related to the presence of neuron groups. This modification allows for a better sharpness and visual resolution. The TRO, areae centrales in the retina, and thin cornea, suggests the need of a well developed visual system resulting from a predatory diet. Rev. Biol. Trop. 57 (4): 1107-1118. Epub 2009 December 01.